IMPLEMENTATION OF MADRASAH E-LEARNING MEDIA IN HISTORY SUBJECTS AT MAN 1 PALU CITY - Windayanti; Hidayati, Siti Zulfa (Tadulako Social Science and Humaniora Journal, 2023)
This paper discusses the application of E-learning madrasah in history subjects at Madrasah Aliyah Negeri 1 Palu City. This research is a qualitative research. The data collection techniques used were observation, interview, and documentation. Qualitative data analysis uses data reduction techniques, data presentation, and conclusions. The implementation of e-learning in History learning in class XI IPS students is to do learning planning in advance by making lesson plans in the form of learning materials, methods used to evaluate learning. In the process of learning history there are several stages including first planning, the teacher prepares a draft online lesson plan (RPP), syllabus, then prepares learning materials in the form of PowerPoint (PPT), and assignments. Second, implementation, the teacher uploads the material and conveys the important points only, then continues the question and answer session, and gives independent assignments that are collected according to the deadline or collection deadline. Third, teachers conduct learning evaluations, such as assessments seen from student learning outcomes, student attitudes and seen from learning practices. In addition, the results of research and interviews that have been conducted show that there are two factors that influence the use of E-Learning, namely supporting factors and inhibiting factors.